2021
DOI: 10.1016/j.physd.2020.132817
|View full text |Cite
|
Sign up to set email alerts
|

Learning dynamical systems from data: A simple cross-validation perspective, part I: Parametric kernel flows

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…A reminder on kernel methods for regularly sampled time series. The simplest approach to forecasting the time series (employed in [22]) is to assume that x 1 , x 2 , . .…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…A reminder on kernel methods for regularly sampled time series. The simplest approach to forecasting the time series (employed in [22]) is to assume that x 1 , x 2 , . .…”
Section: 2mentioning
confidence: 99%
“…, x k−τ † +1 ) to predict future state. Given τ ∈ N * (see [22] for how τ can be learned in practice), the approximation of the dynamical system can then be recast as that of interpolating f † from pointwise measurements…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…The paper will demonstrate also the generalization capabilities of InceptionTime deep Convolutional Neural Networks (CNN) that would allow the cartographic study of analogous albeit not identical dynamical systems. A review of recent machine learning (ML) methods used in dynamical astronomy can be found in 1 , while some advanced techniques to learn dynamical systems can be found in 2 . Our work differentiates from the recent literature on ML for dynamical systems and dynamical astronomy in that we provide some evidence of the ability of DL at classifying types of motion from dynamic indicators associated to time series.…”
Section: Introductionmentioning
confidence: 99%
“…Despite current success of these methods, tackling high-dimensional nonlinear dynamics is still a challenge. This is, because neural networks require an abundance of parameters whose estimation is costly (e.g., due to a non-convex optimization problem), kernel-based methods require a suitable choice of the kernel [HO20], regression methods need the right choice of transformations, making a suitable basis desirable (for instance by restricting the parametrization to collective variables or reaction coordinates [BKK + 17]), and can result in ill-conditioned problems [FWM10]. Lastly, probabilistic models are more stable and do not require strong intuition about the problem, however often suffer from the curse of dimensionality.…”
Section: Introductionmentioning
confidence: 99%